2015
DOI: 10.1080/10640266.2015.1042318
|View full text |Cite
|
Sign up to set email alerts
|

A Brief, Intensive Application of Multi-Family-Based Treatment for Eating Disorders

Abstract: There is a continued need to improve upon the efficacy and avail-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…A retrospective study [64], which compared MFT plus treatment as usual (TAU) to a matched control group receiving only TAU, found that both cases and controls experienced significant weight restoration, but the addition of MFT led to quicker weight gain and higher rates of full weight restoration. Another retrospective study carried out within the framework of an intensive therapeutic program in San Diego [26,65] MFT treatments with a psychoeducational orientation have generated only one comparative study. In a small RCT involving AN adolescent inpatients, Geist et al [32] compared 8 sessions of individual family therapy (FT) with 8 sessions of family group psychoeducation (FGP) over a 4-month study period and found that both treatment modalities equally supported weight restoration, the preference being once more given to FGP because of its better cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study [64], which compared MFT plus treatment as usual (TAU) to a matched control group receiving only TAU, found that both cases and controls experienced significant weight restoration, but the addition of MFT led to quicker weight gain and higher rates of full weight restoration. Another retrospective study carried out within the framework of an intensive therapeutic program in San Diego [26,65] MFT treatments with a psychoeducational orientation have generated only one comparative study. In a small RCT involving AN adolescent inpatients, Geist et al [32] compared 8 sessions of individual family therapy (FT) with 8 sessions of family group psychoeducation (FGP) over a 4-month study period and found that both treatment modalities equally supported weight restoration, the preference being once more given to FGP because of its better cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons is that the model's concepts and techniques draw heavily on the single FBT model [21,22], which has achieved a solid evidence base (for a review of the literature, see [23] ). The Maudsley and Dresden teams have also published detailed descriptions of their MFT theoretical framework and treatment interventions, and developed highly structured and creative training protocols (for AN and BN) which have facilitated its dissemination and encouraged the development of new clinical applications [24][25][26][27][28][29]. Finally, it is important to stress that the Maudsley model has helped challenge theories of family causation (making the family responsible for the ED), taking instead the position that ''the family is not the exclusive or primary factor in the development of the ED'' [30] and that it is a resource rather than a hindrance for recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent 30‐month follow‐up of 74 cases in either single‐family IFT (S‐IFT) or multifamily IFT (M‐IFT), with remission defined as weight at or above 95% of expected for sex, age, and height plus EDE‐Questionnaire global score within 1 SD of norms, and the absence of binge‐purging behaviors, an impressive 88% of participants, regardless of whether they participated in S‐IFT or M‐IFT, achieved remission (Marzola et al, ). While preliminary, IFT shows prosing results and may be a helpful alternative for families who might not otherwise be able to access specialist services, or serve as an ancillary resource for treatment‐resistant cases (Knatz et al, ).…”
Section: What We Do Not Know (Yet)mentioning
confidence: 99%
“…It combines cognitive behavioral therapy (CBT) with systemic-relational intervention, and it is an intensive outpatient treatment aimed to normalize the weight of adolescents affected by AN. The FBT is generally a short clinical program aimed to improve family functioning and to prepare families of adolescents with EDs to support the recovery of the weight in everyday life through educational activities and skills training [58].…”
Section: Therapeutic Approachesmentioning
confidence: 99%